ChemInform Abstract: An Expedient Approach to the Total Synthesis of (+)‐5‐epi‐Eudesm‐4(15)‐ene‐1β, 6β‐diol. Issue 12 (14th March 2013) - Parthasarathy, Gowrisankar; Besnard, Celine; Kuendig, E. Peter
Abstract The title compound (V) is synthesized via an Ireland—Claisen rearrangement of glycolate ester (I) and an intramolecular nitrile oxide cycloaddition [→ (IV)] as key steps.